Decoupling of soil nutrient cycles as a function of aridity in global drylands - Delgado-Baquerizo, Manuel; Maestre, Fernando; Gallardo, Antonio; Bowker, Matthew; Wallenstein, Matthew; Quero, Jose Luis; Ochoa, Victoria; Gozalo, Beatriz; García-Gómez, Miguel; Soliveres, Santiago; García-Palacios, Pablo; Berdugo, Miguel; et al. (Nature, 2013)
The biogeochemical cycles of carbon (C), nitrogen (N) and phosphorus (P) are interlinked by primary production, respiration and decomposition in terrestrial ecosystems1. It has been suggested that the C, N and P cycles could become uncoupled under rapid climate change because of the different degrees of control exerted on the supply of these elements by biological and geochemical processes1–5. Climatic controls on biogeochemical cycles are particularly relevant in arid, semi-arid and dry sub-humid ecosystems (drylands) because their biological activity is mainly driven by water availability6–8. The increase in aridity predicted for the twenty-first century in many drylands worldwide9–11 may therefore threaten the balance between these cycles, differentially affecting the availability of essential nutrients12–14. Here we evaluate how aridity affects the balance between C, N and P in soils collected from 224 dryland sites from all continents except Antarctica. Wefind a negative effect of aridity on the concentration of soil organic C and total N, but a positive effect on the concentration of inorganic P. Aridity is negatively related to plant cover, which may favour the dominance of physical processes such as rock weathering, a major source of P to ecosystems, over biological processes that provide more C and N, such as litter decomposition12–14. Our findings suggest that any predicted increase in aridity with climate change will probably reduce the concentrations of N and C in global drylands, but increase that of P. These changes would uncouple the C, N and P cycles in drylands and could negatively affect the provision of key services provided by these ecosystems. European Commission Ministerio de Ciencia e Innovación (España) Programa Iberoamericano de Ciencia y Tecnología para el Desarrollo Universidad Pablo de Olavide Depto. de Biodiversidad, Ecología y Evolución Fac. de Ciencias Biológicas TRUE pub